2010
DOI: 10.1007/s12041-010-0053-7
|View full text |Cite
|
Sign up to set email alerts
|

SSR mining in oil palm EST database: application in oil palm germplasm diversity studies

Abstract: This study reports on the detection of additional expressed sequence tags (EST) derived simple sequence repeat (SSR) markers for the oil palm. A large collection of 19243 Elaeis guineensis ESTs were assembled to give 10258 unique sequences, of which 629 ESTs were found to contain 722 SSRs with a variety of motifs. Dinucleotide repeats formed the largest group (45.6%) consisting of 66.9% AG/CT, 21.9% AT/AT, 10.9% AC/GT and 0.3% CG/CG motifs. This was followed by trinucleotide repeats, which is the second most a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
51
8
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 23 publications
11
51
8
4
Order By: Relevance
“…The mean H o and H e values in this study was 0.6296 and 0.7616, respectively, higher compared to those reported by Ting et al (2010) (0.400 and 0.437, respectively) using 15 SSR markers and Bakoumé et al (2015) (0.460 and 0.644, respectively) using 16 SSR markers. These high mean values of H o and H e depicted the high genetic variability in the oil palm samples evaluated in this study notwithstanding that the materials have undergone some selection and breeding activities.…”
Section: Observed Heterozygosity (H O ) and Expected Heterozygosity (contrasting
confidence: 77%
See 1 more Smart Citation
“…The mean H o and H e values in this study was 0.6296 and 0.7616, respectively, higher compared to those reported by Ting et al (2010) (0.400 and 0.437, respectively) using 15 SSR markers and Bakoumé et al (2015) (0.460 and 0.644, respectively) using 16 SSR markers. These high mean values of H o and H e depicted the high genetic variability in the oil palm samples evaluated in this study notwithstanding that the materials have undergone some selection and breeding activities.…”
Section: Observed Heterozygosity (H O ) and Expected Heterozygosity (contrasting
confidence: 77%
“…Open pollination that prevails in the natural oil palm groves whereby an oil palm tree receives pollens from many donor trees contributes to increasing allelic diversity. Results of the present study (H e = 0.347) and the previous study by Ting et al (2010; H e = 0.340) revealed the presence of low genetic variation among MPOB Deli dura. The Deli dura has undergone several cycles of selection compared to NIFOR Deli dura.…”
Section: Observed Heterozygosity (H O ) and Expected Heterozygosity (supporting
confidence: 58%
“…Also, [16] revealed even lower values (He = 0.340) for Deli dura via 15 EST-SSRs. Recently, [15] reported Ho values (0.310 and 0.211) and He values (0.549 and 0.559) for Deli dura MPOB (Malaysia) and Deli dura Dabou (Côte d'Ivoire) with 16 microsatellite markers.…”
Section: Amplification Of Ssr Markermentioning
confidence: 93%
“…When compared to the previous report of Cochard et al (2009), lower values of expected heterozygosity (H e = 0.373) for Deli NIFOR and (H e = 0.510) for 6 Deli dura populations from different origins using 14 SSR markers. Also, Ting et al [51] revealed even lower values (H e = 0.340) for Deli dura via 15 EST-SSRs. Recently, Bakoume et al [38] reported H o values (0.310 and 0.211) and H e values (0.549 and 0.559) for Deli dura MPOB (Malaysia) and Deli dura Dabou (Côte d'Ivoire) with 16 microsatellite markers.…”
Section: Observed Heterozygosity and Expected Heterozygosity In The Tmentioning
confidence: 95%
“…The number of alleles per locus is affected by the number of markers and sample size analyzed. Singh et al [39] previously reported lower number of alleles per locus (2.2 -3.2) in E. guineensis germplasm using a smaller set of SSRs and the number of alleles increased (2.8 -3.9) when Ting et al [51] employed a larger set of SSRs to evaluate a wider pool of oil palm germplasm. In fact, Augustina et al [73] reported a total of 163 alleles (mean = 8.2) among the 85 pisifera accessions from germplasm collections of different origins at Sampoerna Agro Tbk (SA) in Indonesia.…”
Section: Mean Number and Effective Number Of Alleles Per Locusmentioning
confidence: 99%